Short and Sweet: D‐Glucose to L‐Glucose and L‐Glucuronic Acid1. Issue 4 (5th December 2013) - Martínez, R. Fernando; Liu, Zilei; Glawar, Andreas F. G.; Yoshihara, Akihide; Izumori, Ken; Fleet, George W. J.; Jenkinson, Sarah F.
Abstract The scarcity and expense of access to L‐sugars and other rare sugars have prevented the exploitation of their biological potential; for example D‐psicose, only recently available, has been recognized as an important new food. Here we give the definitive and cheap synthesis of 99.4% pure L‐glucose from D‐glucose which requires purification of neither intermediates nor final product other than extraction into and removal of solvents; a simple crystallization will raise the purity to >99.8%.